Early specialization and recomendations for swimming - Mattila, R. (Haaga-Helia University of Applied Science, 2018)
The present work was done to investigate the literature to see what does the literature say about specialization in swimming, to get perspective and learn from other sports and to make a material for Finnish Swimming Association (Suomen Uimaliitto). Based on the literature, the purpose was to make an educational material for the Finland`s Swimming Association which they can use for coaches education, athlete development and long-term development how they see fit.